The influence of flavancontent means on gut mucosa state at rats received peroxide sunflower oil - Bocharov, A. V. (Journal of Education, Health and Sport, 2018)
Aim: To investigate influence of flavancontent antidysbiotic means in gut mucosa state at rats, received peroxide sunflower oil (PSO).Materials and methods: Rats received PSO daily in dose 1 ml duration 2,5 mounts. From 31-th day of the experiment rats received flavancontent means (quertulin, lequin, lekasil) in dose 300 mg/kg. The activities elastase, urease, catalase and content of MDA were deter-mined into gut mucosa.Results: The activities elastase, urease and content of MDA were increased in rats re-ceived PSO, but activities lysozyme and catalase were reduced. The flavancontent means were lowered the activities of elastase, urease and content of MDA, but were increased activi-ties lysozyme and elastase.Conclusion: PSO made dysbiosis and inflammation in gut mucosa. Flavancontent means mode mucosoprotective action.